Airborne Assault on Corregidor: A Study in Weather, Terrain, and Cultural Landscapes - Lohman, Andrew D (Scientia Militaria - South African Journal of Military Studies, 2018)
In many ways, military forces using advanced technologies have been able to overcome a number of the inherent and traditional challenges posed by physical geography. However, geography continues to play a significant role in military planning and operations in two areas that have received little attention in the literature, namely airborne operations and the cultural landscape. This case study sought to contribute to these discussions by analysing the American operation to seize Corregidor Island in February 1945. As a primarily airborne assault, the operation was heavily contingent on weather, but also on terrain for sufficient drop zones, and the cultural landscape and terrain intelligence of the American forces proved vital in this regard. Through analysing archival military planning documents, maps, images and other primary and secondary sources, this study found that the physical terrain and enemy defences dictated the overall plan, but two features of the cultural landscape, the parade ground and golf course, were essential to the airborne operation, serving as the smallest drop zones used in World War II by US forces. While these two spaces enabled the assault, their small size, the buildings surrounding them, and the prevailing winds made this mission the most dangerous and highest jump casualty airborne operation of the war. Despite the casualties incurred by these features, the bombed-out buildings and debris on the drop zones arguably prevented even greater casualties because of the cover these provided once paratroopers were assembled on the ground. The intent of this discussion is to demonstrate how airborne operations are inherently contingent on geography and the challenges and opportunities the cultural landscape could pose during a military operation.